177k views
0 votes
Help, please! I appreciate you taking the time to help me
question attached

Help, please! I appreciate you taking the time to help me question attached-example-1
User Simmy
by
4.5k points

1 Answer

4 votes
F(gx)
f(-x-4) = 2(-x-4) + 3
F(-x-4)= -2x-8+3
F(-x-4)= -2x-5

G(fx)
G(2x+3)= -(2x+3) -4
G(2x+3)= -2x-3-4
G(2x+3)= -2x-7

F(hx)
F(x^2)=2x^2+3

H(fx)
H(2x+3)= (2x+3)^2
H(2x+3)= (2x^2) + 2(2x)(3)+3^2
H(2x+3)= 4x^2+12x+9

[I think I messed up with the last one. I didn’t know how to get the correct answer for that. Sorry ]
User Feathercrown
by
4.8k points